Tuning the interlayer spacing of forward osmosis membranes based on ultrathin graphene oxide to achieve desired performance. (February 2019) - Hung, Wei-Song; Chiao, Yu-Hsuan; Sengupta, Arijit; Lin, Ya-Wen; Wickramasinghe, S. Ranil; Hu, Chien-Chieh; Tsai, Hui-An; Lee, Kueir-Rarn; Lai, Juin-Yih
Abstract: Forward osmosis membranes based on ultrathin graphene oxide (GO) were fabricated. Suitable crosslinking agents were used to tune the interlayer spacing of GO sheets to achieve the desired membrane performance. The physicochemical properties of membranes were evaluated using different techniques. The interlayer spacing of GO-based membranes was controlled the interaction between the surface functionality of GO with the nature of crosslinking agents, such as polyvinyl alcohol, meta-phenylenediamine (MPD) and 1, 3, 5-benzenetricarbonyl chloride (TMC). The covalent bonds between the layer and crosslinking agents effectively suppressed the d-spacing stretching. Unlike other symmetric structures of membranes, the GO-MPD/TMC behaviour observed in the ultrathin polyamide (36 nm) asymmetric structure for the performance of pressure-retarded osmosis (PRO) mode showed the highest flux of 20.8 LMH and low reverse salt flux of 3.4 gMH. A consistent water flux for a long-term PRO operation was achieved using GO-MPD/TMC membrane (∼98.7%). Therefore, the GO-MPD/TMC membrane can be used to suppress internal concentration polarisation. Graphical abstract: The GO-MPD/TMC behaviour observed in the ultrathin polyamide (36 nm) asymmetric structure showed the highest flux of 20.8 LMH and low reverse salt flux of 3.4 gMH. A consistent water flux for a long-term operation was achieved using GO-MPD/TMC membrane (∼98.7%). Therefore, the ultrathin graphene oxide framework membrane may be used to suppress internal concentration polarisation. Image 1